Multifunctional prospects of physical vapor-deposited silver-based metal-dielectric nanocomposite thin films - Mohammad Nur-E-Alam; Boon Kar Yap; Mohammad Khairul Basher; Mohammad Aminul Islam; M. Khalid Hossain; Manzoore Elahi M. Soudagar; Narottam Das; Mikhail Vasiliev; Tiong Sieh Kiong (Journal of Science: Advanced Materials and Devices)
Silver-based metallic thin-film nanostructured materials are extensively utilized in advanced technological applications, including sensors, energy-efficient coatings, antibacterial coatings, and optical filters. Physical vapor deposition has emerged as a significant technique for synthesizing silver (Ag)-based nanocomposites, enabling the modification of structural and optical properties of thin metallic films. This advancement facilitates material development and applications in electronics, catalysis, magnetics, optics, environmental and health sectors, and specialized optical coatings. Research has demonstrated the successful integration of various nanomaterials with Ag matrices, resulting in multifunctional thin-film systems. Ag-based nanocomposite thin films exhibit exceptional electrical conductivity, rendering them suitable for electronic and optoelectronic devices. Their unique optical properties enable applications in advanced photonics, spectroscopy, and imaging technologies. These films also demonstrate potential in catalysis, power conversion and storage, environmental remediation, and chemical sensing. The incorporation of antimicrobial agents presents opportunities for biomedical applications. This review aims to comprehensively examine the synthesis, characterization, and potential applications of physically vapor-deposited Ag-based nanocomposite thin films, highlighting their promising future in various fields.